2010
DOI: 10.1111/j.1440-1681.2009.05261.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 MSPI (T6235C) gene polymorphism is associated with mortality in acute coronary syndrome patients

Abstract: 1. The CYP1A1 T6235C polymorphism (rs4646903) gene polymorphism has been linked to the development of coronary heart disease and cigarette smoking-related lung cancer. The present study investigated associations between survival in acute coronary syndromes (ACS), smoking and the CYP1A1 T6235C polymorphism. 2. Patients with ACS (n = 1251) were genotyped for the CYP1A1 T6235C polymorphism. Patients had a mean age of 67.0 years, 69.8% were male and follow up occurred over a median of 1.9 years. 3. Overall genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
0
8
1
Order By: Relevance
“…This attribute highlighted the importance of the association between heart diseases and CYP1A1 polymorphisms [138140]. …”
Section: Cyp1a1 Through Developmentmentioning
confidence: 99%
“…This attribute highlighted the importance of the association between heart diseases and CYP1A1 polymorphisms [138140]. …”
Section: Cyp1a1 Through Developmentmentioning
confidence: 99%
“…3 Other studies have implicated other genetic variants as markers of the risk of development of ACS and clinical outcome during progression of the disease. [25][26][27] The frequency of rs697829 alleles in this cohort was similar to populations of European ancestry in the National Center for Biotechnology Information SNP database, http://www.ncbi.nlm.nih.gov/snp (dbSNP). Allele frequency was significantly associated with ethnicity, but this was largely due to differences between the predominant European group and the small Other and Unknown groups ( Table 2).…”
Section: Discussionmentioning
confidence: 51%
“…We have previously shown that a polymorphism in the X‐linked gene ACE2 was associated with covariate‐adjusted, but not unadjusted, survival in a cohort of male ACS patients 3 . Other studies have implicated other genetic variants as markers of the risk of development of ACS and clinical outcome during progression of the disease 25–27 …”
Section: Discussionmentioning
confidence: 96%
“…The search criteria identified 38 abstracts. Following elimination of studies that did not meet the criteria and exclusion of 19 records, 9 full-text publications were preliminarily identified for further evaluation (11)(12)(13)(14)(15)(16)(27)(28)(29). Each original manuscript was reviewed and data were extracted.…”
Section: Resultsmentioning
confidence: 99%